Context in Cultural and Literary Studies - Ladegaard, Jakob; Gaardbo Nielsen, Jakob (Comparative Literature and Culture, 2019)
Context in Literary and Cultural Studies is an interdisciplinary volume that deals with the challenges of studying works of art and literature in their historical context today. The relationship between artworks and context has long been a central concern for aesthetic and cultural disciplines, and the question of context has been asked anew in all eras. Developments in contemporary culture and technology, as well as new theoretical and methodological orientations in the humanities, once again prompt us to rethink context in literary and cultural studies. This volume takes up that challenge. Introducing readers to new developments in literary and cultural theory, Context in Literary and Cultural Studies connects all disciplines related to these areas to provide an interdisciplinary overview of the challenges different scholarly fields today meet in their studies of artworks in context. Spanning a number of countries, and covering subjects from nineteenth-century novels to rave culture, the chapters together constitute an informed, diverse and wide-ranging discussion.